Speech Act: Analyzing Pragmatics Phenomenon Occurrences in Doctor Strange Movie - Salsabila, Annisa; Saputra, I Gede; Goteji, Wendy (English Language Education, Universitas Internasional Batam, 2021)
The use of Semantic and Pragmatics are not limited to a written text only, but they can be of use in the verbal industry. Such as speech, movies, and other verbal activities events. Several theories discussed how we can analyze a movie with Semantic and Pragmatics. One of them is using the action of utterances as one of the ways to know the phenomenon occurrences or we called them as Speech Act.For this study, the researcher uses the conversation between each character with their target speech in the movie as the object of research, meanwhile, the characters who play the role in the movie will work as the subject. The researcher uses Qualitative Descriptive, and the results will be described in a term. The results indicate that there are several forms, functions, effects, situations, and classifications of speech acts in the movie â€œDoctor Strangeâ€.